Fine Needle Aspiration Cytology of Ovarian Tumors With Histopathological Correlation: A Revisit to Borderline Category - Zoya Hasan; Meeta Singh; Jyoti Singh; Gautam Chellani; Irfana Nisam; Garima Rakheja; Shyama Jain; Nita Khurana; Shramana Mandal; Arun K. Rathi; Yedla M. Mala; Radhika Batra (Journal of Cytology)
Background: Borderline ovarian tumors (BOTs) comprise 15%–20% of all ovarian epithelial malignancies. The majority of them are serous tumors followed by mucinous tumors. Pre-operative cytological diagnosis plays an important role with histopathology being the gold standard. The present study aimed to assess the sensitivity, specificity, and diagnostic accuracy of cytology in the diagnosis of epithelial ovarian tumors with special emphasis on the cytologically borderline category. Materials and Methods: The present study was conducted in our institute over five years from January 2017 to December 2022. This was a retrospective study and included 92 patients with ovarian masses who were subjected to ultrasound-guided fine needle aspiration (FNA) as a preliminary diagnostic procedure. Cytology smears were examined and categorized as benign, borderline, and malignant. The sensitivity, specificity, and diagnostic accuracy were assessed considering histopathology as the gold standard. Results: In the present study, 92 ovarian FNA cytology were performed. Aspirates were adequate in all but 10 cases. Out of 82 cases, 75 were epithelial tumors. Twelve cases of BOTs were compiled and cytological findings were assessed. Conclusion: To conclude, diagnosis of BOTs on cytology is difficult, however, aspiration from multiple sites from the lesion, critical cytomorphological assessment, and cell-block preparation with immunocytochemistry/immunohistochemistry can overcome the pitfalls.